2020
DOI: 10.1038/s41587-020-0513-4
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR–Cas12-based detection of SARS-CoV-2

Abstract: An outbreak of betacoronavirus severe acute respiratory syndrome (SARS)-CoV-2 began in Wuhan, China in December 2019. COVID-19, the disease associated with SARS-CoV-2 infection, rapidly spread to produce a global pandemic. We report development of a rapid (<40 min), easy-to-implement and accurate CRISPR-Cas12-based lateral flow assay for detection of SARS-CoV-2 from respiratory swab RNA extracts. We validated our method using contrived reference samples and clinical samples from patients in the United States, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
2,267
1
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,212 publications
(2,444 citation statements)
references
References 21 publications
39
2,267
1
23
Order By: Relevance
“…30 The DETECTR assay by Mammoth Biosciences relies on the cleavage of reporter RNA by Cas12a to specifically detect viral RNA sequences of the E and N genes, followed by isothermal amplification of the target, resulting in a visual readout with a fluorophore. 31 These CRISPR-based methods, as depicted in Figure 3, do not require complex instrumentation and can be read using paper strips to detect the presence of the SARS-CoV-2 virus without loss of sensitivity or specificity. These tests are both low-cost and can be performed in as little as 1 h. These tests have great potential for point-of-care diagnosis.…”
Section: Reverse Transcription Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
“…30 The DETECTR assay by Mammoth Biosciences relies on the cleavage of reporter RNA by Cas12a to specifically detect viral RNA sequences of the E and N genes, followed by isothermal amplification of the target, resulting in a visual readout with a fluorophore. 31 These CRISPR-based methods, as depicted in Figure 3, do not require complex instrumentation and can be read using paper strips to detect the presence of the SARS-CoV-2 virus without loss of sensitivity or specificity. These tests are both low-cost and can be performed in as little as 1 h. These tests have great potential for point-of-care diagnosis.…”
Section: Reverse Transcription Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
“…They showed that Cas12b behaves similarly to Cas12a for ssDNA reporter cleavage and can achieve a detection limit of 5 copies/ L in 40-60 minutes . Moreover, Broughton et al used LAMP instead of RPA in DETECTR and further reduced the testing time for SARS-CoV-2 RNA to 30-32 minutes while maintaining a low detection limit (10 copies/ L) (Broughton et al 2020).…”
Section: Crispr-based Detectionmentioning
confidence: 99%
“…LAMP has been used to detect many pathogens including Zika virus [3], Mycobacterium tuberculosis [4], malaria [5], and human leishmaniasis [6]. RT-LAMP has also been performed on extracted RNA for subsequent CRISPR-Cas12-based detection of SARS-CoV-2 [7].…”
Section: Introductionmentioning
confidence: 99%